Using Swallowing Quality of Life to Compare Oropharyngeal Dysphagia Following Cervical Disc Arthroplasty or Anterior Cervical Discectomy and Fusion - Mohan, Shruthi; Jadczak, Caroline N; Cha, Elliot D K; Lynch, Conor P; Patel, Madhav R; Jacob, Kevin C; Pawlowski, Hanna; Prabhu, Michael C; Vanjani, Nisheka N; Singh, Kern (Journal of minimally invasive spine surgery and technique, 2022)
Objective: To evaluate dysphagia outcomes using the swallowing quality of life (SWAL-QOL) questionnaire between patients undergoing cervical disk arthroplasty (CDA) or anterior cervical discectomy and fusion (ACDF).Methods: A retrospective review of a prospective surgical database was performed to identify individuals who underwent cervical procedures between 2014 and 2020. Patient-reported outcome measures (PROMs) were collected using SWAL-QOL, VAS, NDI, and SF-12 PCS. All measures were recorded at the preoperative to 6-month postoperative timepoint. Patients were grouped according to cervical procedure and instrumentation used. Differences in PROMs and SWAL-QOL domains were evaluated by t-test and one-way ANOVA with post-hoc testing, respectively. Simple linear regression was employed to evaluate the relationship between number of levels operated on and postoperative outcomes. Results: A total of 161 patients were included. ACDF and CDA patients demonstrated no significant differences in VAS neck and arm, or NDI at any timepoint. However, CDA patients had significantly worse SWAL-QOL scores at 6-months. Preoperative VAS neck was significantly worse for patients who underwent either an ACDF procedure with a stand alone cage or CDA as compared to patients who underwent an ACDF with anterior plating. At 6-months postoperatively, CDA patients reported a significantly worse “fatigue” score compared to ACDF patients. At 6-months postoperatively, ACDF patients reported a significantly better “sleep” scores compared to CDA patients with both recipients of an anterior plate and stand alone cage reporting significantly better scores compared to the CDA cohort (p=0.024; p<0.001). No postoperative outcome studied was significantly associated with number of levels operated on, other than the SWAL-QOL domain of symptom frequency at the 6-week postoperative time point (p=0.032). Conclusion: Patients undergoing either an ACDF or CDA procedure largely did not demonstrate differences in pain, disability, and dysphagia scores. However, at more longitudinal timepoints CDA patients reported worse fatigue and sleep scores compared to ACDF patients.